Особливості посвідчення довіреностей, прирівнюваних до нотаріально посвідчених, посадовими та службовими особами закладів охорони здоров’я України - Долинська, Марія; Dolynska, Maria; Долинская, Мария (Видавництво Львівської політехніки)
Розглянуто особливості посвідчення довіреностей, прирівнюваних до нотаріально посвідчених, посадовими та службовими особами закладів охорони здоров’я України. Проаналізовано нормативні акти, які регулюють порядок укладення та посвідчення довіреностей, прирівнюваних до нотаріально посвідчених, зокрема, уповноваженими на це посадовими та службовими особами закладів охорони здоров’я. Досліджено поняття довіреностей, а також здійснено їх класифікацію. Посвідчення довіреностей посадовими та службовими особами закладів охорони здоров’я України, переліченими у статті 40 Закону України “Про нотаріат”, повинно відбуватися із дотриманням норм чинного українського законодавства, зокрема норм Цивільного кодексу України, Земельного кодексу України, Закону України “Про нотаріат”, Порядку посвідчення заповітів і довіреностей, що прирівнюються до нотаріально посвідчених, а також інших нормативно-правових актів. Окрему увагу автором приділено змісту довіреностей. У статті також розглянуто порядок припинення та скасування нотаріально посвідченої довіреності.

The peculiarities of certification of powers of attorney that equal to notarial by public individuals and official persons of health care establishments of Ukraine are considered. In the article the analysis of normative acts, regulating the procedure for testamentation and certification of powers of attorney that equal to notarial, including by authorized individual officials and official persons of healthcare care establishments, is made. The concept of powers of attorney is investigated and their classification is carried out. The author states that public individuals and official persons of health care establishments of Ukraine who certify the powers of attorney that equal to notarial, are not entitled to certify powers of attorney in their name and on behalf of their name, as well as in the name of and on behalf of his wife or her husband. Specified public individuals, official persons have also no right to perform powers of attorney in the name of their sons and daughters, mother, father, grandchildren, grandfather, grandmother, including their brothers or sisters. Analyzing the issue of the certification of the power of attorney to make a donation contract on behalf of the patient, the author emphasizes the necessity to indicate the name of donee. While certifying the powers of attorney public individuals, official persons of health care establishments of Ukraine, listed in Article 40 of the Law of Ukraine “On Notariate”, should strictly adhere to the norms of the current legislation, in particular the norms of the Civil Code of Ukraine, the Land Code of Ukraine, the Law of Ukraine “On Notariate”, the Procedure of certifying wills and powers of attorney that equal to notarial, as well as other normative and legal acts. The author pays special attention to the content of powers of attorney. The procedure for termination and cancellation of a notarized power of attorney is examined.

Рассматриваются особенности удостоверения доверенностей, приравниваемых к нотариально удостоверенным, должностными и служебными лицами учреждений здравоохранения Украины. В статье осуществлен анализ нормативных актов, регулирующих порядок заключения и удостоверения доверенностей, приравниваемых к нотариально удостоверенным, в частности, уполномоченными на это должностными и служебными лицами учреждений здравоохранения. В статье исследовано понятие доверенностей, а также осуществлена их классификация. Удостоверение доверенностей, должностными и служебными лицами учреждений здравоохранения Украины, перечисленными в статье 40 Закона Украины “О нотариате”, должно происходить с соблюдением норм действующего украинского законодательства, в частности норм Гражданского кодекса Украины, Земельного кодекса Украины, Закона Украины “О нотариате”, Порядка удостоверения завещаний и доверенностей, которые приравниваются к нотариально удостоверенным, а также других нормативно-правовых актов. Особое внимание автором уделено содержанию доверенностей. В статье также рассмотрен порядок прекращения и отмены нотариально удостоверенной доверенности.
Special features of certification of powers of attorney that equal to notarial by public individuals and official persons of health care establishments of Ukraine
Особенности удостоверения доверенностей, приравниваемых к нотариально удостоверенным, должностными и служебными лицами учреждений здравоохранения Украины
Keywords: посадові та службові особи закладів охорони здоров’я; довіреності; прирівнювані до нотаріально посвідчених; public individuals and official persons of health care establishments; powers of attorney that equal to notarial; должностные и служебные лица учреждений здравоохранения; доверенности; приравниваемые к нотариально удостоверенным; 340; 12